Adopting strategies of mobile technology for assisted learning performance in higher education in China - Yuan, Ruichen; Ab Jalil, Habibah; Omar, Muhd Khaizer (Elsevier, 2025)
Mobile technology, particularly mobile-assisted learning, has long been a rapidly growing and dynamic field. A prominent focus within this domain is the development and implementation of mobile learning applications and systems. The widespread adoption of mobile learning has led to the emergence of numerous applications, granting higher education students increased autonomy in leveraging mobile devices to support their academic performance. However, the abundance of available options has made the strategic selection and effective use of appropriate applications a pressing issue. This study employed a mixed-methods approach to investigate strategies for adopting mobile learning applications in Chinese higher education institutions—a context in which limited research has been conducted despite the ongoing technological transformation in mainland China. The findings revealed that academic major significantly influenced students’ learning performance supported by mobile applications, primarily due to differing academic demands [F(11, 289) = 1.788, p = .056, η² = 0.064]. Learners’ positive perceptions of mobile learning applications were found to be crucial to their assisted learning outcomes. Moreover, most students acknowledged the necessity of receiving guidance when selecting learning applications. Among the various forms of support examined, teacher recommendations were particularly valued. However, both in-class and out-of-class support remained insufficient. While online searches and social media offer some assistance, there is a strong preference among students for direct guidance from instructors. Furthermore, existing mobile learning applications do not fully meet the diverse needs of all learners. To address these challenges, this study proposes an eight-stage adoption strategy aimed at enhancing university students’ learning performance through more effective use of mobile applications.